Media dan Mitos: Framing Kusni Kasdut Sebagai Legenda Kriminal - Fajar Kurniawan; RR. Rosita Cindrakasih; Angghi Muliya Ma’mur; Hani Yuniani (Jurnal Ragam Pengabdian, 2026)
This article analyzes the dynamics of the myth-making of Kusni Kasdut (1929–1980) through the lens of mass media framing in the 1960s–1980s in the context of postcolonial Indonesia. As a former freedom fighter turned legendary robber, Kusni occupies an ambiguous position between criminality and heroism that triggers a narrative battle between the state and the lower classes. This research uses critical discourse analysis (Fairclough, 2015) and myth-narrative analysis (Campbell, 2020; Turner, 2017). Critical discourse analysis of national and local media coverage, including Kompas and Tempo, as well as official documents and oral sources from the Gang Jangkrik community in Malang and Surabaya. This research explores 32 national and local media articles and interviews with four key informants from the Gang Jangkrik community in Malang and Surabaya. The findings show that the media constructed three dominant frames: (1) criminality as a threat to the state, (2) heroism as an "Indonesian Robin Hood," and (3) ambiguity as a criminal legend. On the one hand, the official narrative emphasizes recidivism and serious crimes; on the other, news reports detailing his ingenuity, escape skills, and revolutionary background inadvertently reinforce his legendary aura. The myth of the "Indonesian Robin Hood" that has developed in society's collective memory functions as a form of counter-hegemony against the state's claims of moral monopoly. Kusni represents the phenomenon of postcolonial urban criminal legends that reflect the failure of state modernization to integrate marginalized groups, particularly disabled veterans. This study contributes to an understanding of the relationship between media, power, and myth-making in a society experiencing a crisis of legal legitimacy.